Light In The Dark Azyumardi Azra's Cotribution In Framing Novelty of Nusantara Islam - Martinus Joko Lelono (Journal of Asian Orientation in Theology, 2023)
Azyumardi Azra significantly contributed to re-framing the Indonesian situation during his lifetime as a scholar. This article works on the literature review of the works of Azra. It aims to perform an analytical article that helps people comprehend that social reality lives in certain identity politics. Azra proposed to look at reality from the "Optimistic Perspectiveâ€ that has become a distinguished perspective in looking at the present situation of Indonesian Islam. Using the social framing theory by Erving Goffman, this article contributes to performing the social life from a new perspective. In the Catholic perspective of interreligious dialogue, the work of Azyumardi Azra is in line with the contemporary efforts of Pope Francis. As an institution, a religion derives into a certain situation that emerges the complexity of its adherentsâ€™ way of thinking, however, certain influential figures build new social frameworks that enable people to have a distinctive way from the directed situation.Â